Patient preferences in tinnitus outcomes and treatments: a qualitative study*. (3rd October 2018) - Pryce, Helen; Hall, Amanda; Shaw, Rachel; Culhane, Beth-Anne; Swift, Sarah; Straus, Jean; Claesen, Beth
Abstract: In order to identify patient preferences in care for tinnitus an in depth grounded theory study was conducted. This consisted of interviews with 41 patients who had sought help for tinnitus across a range of locations and tinnitus services in England. Preferences for outcomes were for both the removal of the tinnitus and for improved coping and management of the tinnitus. Preferences for treatment were for individualized care, tailored information and for treatment to assist with psychological adjustment and auditory distraction. Adoption of treatments to manage tinnitus were based on a trial and error approach. Patients? preferences for individual treatments varied but were informed by the information they received. Information plays an important role in care for people with tinnitus. Patients hold individual preferences and require engagement in shared decision making.